Scattered-fields-induced tunable narrow resonance in low-index dielectric meta-lattices for transflective display - Suhandoko D. Isro; Agoes Soehianie; Alexander A. Iskandar (Journal of Information Display)
The development of a transflective display is important for reducing the energy consumption of an outdoor display-device. Currently, it is desirable to have a transflector which can be switched between its reflective and transparent states. The present work provides a novel yet simple route for the development of such a transflector based on one-dimensional (1D) meta-lattice systems. The system studied is shown capable of exciting tunable narrow resonance in the reflectance spectra through the generation of the scattered-field-induced polarizing-field in the system. Surprisingly, while most work on dielectric metasurface relies on high-index material, here it is found that the phenomenon can be achieved with common low-index material. Hence, it is a promising alternative for the development of future display technology with more economical operational cost.